2005
DOI: 10.1007/s00604-005-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Two-Phase Clean-Up System in Food Samples Prior to Fluorescence Analysis of Aflatoxins

Abstract: Abstract.A new method based on the use of a twophase separation system is proposed for the clean-up of aflatoxins after their extraction from food samples. After extraction from the sample with an appropriate solvent, aflatoxins contained in organic solvent diffuse to the aqueous phase. At that stage their relative concentration is measured fluorimetrically at 350 nm ( exc ). Different organic solvents were tested, and the composition of the aqueous phase was varied. The data obtained showed that the best effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In all analysed samples no AFs were found [48]. Bourais et al [46] recently reported a two-phase clean up system for AFs in food samples. In the first step, the samples were extracted with an organic solvent (MeOH) and then the solvent was evaporated and redissolved in toluene.…”
Section: Extraction and Clean Up Techniquesmentioning
confidence: 83%
See 2 more Smart Citations
“…In all analysed samples no AFs were found [48]. Bourais et al [46] recently reported a two-phase clean up system for AFs in food samples. In the first step, the samples were extracted with an organic solvent (MeOH) and then the solvent was evaporated and redissolved in toluene.…”
Section: Extraction and Clean Up Techniquesmentioning
confidence: 83%
“…The quantification of the AFs was carried out by direct fluorescence measurement at 350 nm without chromatographic separation. A LOD of 0.3 lg/kg and recoveries ranging 86 -104% for AFB 1 and 95 -100% for AFM 1 were obtained [46]. The authors have mentioned that using chloroform for initial extraction obtained good recoveries.…”
Section: Extraction and Clean Up Techniquesmentioning
confidence: 96%
See 1 more Smart Citation
“…Human and animal liver is the main target organ of toxicity and carcinogenicity (Giray et al 2007;Aycicek et al 2005). The order of toxicity of aflatoxins, AFB 1 > AFG 1 > AFB 2 > AFG 2 seems to stem from its structure; the portion of AFB1 terminal furan is the critical point for determining the degree of biological activity of this group of mycotoxins (Bourais et al 2006, Chiavaro et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, aflatoxins contaminate those foodstuffs with a high proportion of carbohydrates and lipids (Nilufer and Boyacioglu 2002) such as nuts (peanuts, pistachios, walnuts), dried fruits (figs), corn (maize), spices (pepper), seeds, milk, cocoa, beer (Cavaliere et al 2007, Bourais et al 2006, Nilufer and Boyacioglu 2002, Stroka et al 2000.…”
Section: Introductionmentioning
confidence: 99%